Evaluation of a SARS-CoV-2 Surrogate Virus Neutralization Test for Detection of Antibody in Human, Canine, Cat, and Hamster Sera - Perera, Ranawaka A. P. M.; Ko, Ronald; Tsang, Owen T. Y.; Hui, David S. C.; Kwan, Mike Y. M.; Brackman, Christopher J.; To, Esther M. W.; Yen, Hui-ling; Leung, Kathy; Cheng, Samuel M. S.; Chan, Kin Ho; Chan, Karl C. K.; et al. (Journal of clinical microbiology, 2021)
Surrogate neutralization assays for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that can be done without biosafety level 3 containment and in multiple species are desirable. We evaluate a recently developed surrogate virus neutralization test (sVNT) in comparison to 90% plaque reduction neutralization tests (PRNT 90 ) in human, canine, cat, and hamster sera. With PRNT 90 as the reference, sVNT had sensitivity of 98.9% and specificity of 98.8%. Using a panel of immune sera corresponding to other coronaviruses, we confirm the lack of cross-reactivity to other coronaviruses in SARS-CoV-2 sVNT and PRNT 90 , except for cross-reactivity to SARS-CoV-1 in sVNT. Surrogate neutralization assays for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that can be done without biosafety level 3 containment and in multiple species are desirable. We evaluate a recently developed surrogate virus neutralization test (sVNT) in comparison to 90% plaque reduction neutralization tests (PRNT 90 ) in human, canine, cat, and hamster sera. With PRNT 90 as the reference, sVNT had sensitivity of 98.9% and specificity of 98.8%. Using a panel of immune sera corresponding to other coronaviruses, we confirm the lack of cross-reactivity to other coronaviruses in SARS-CoV-2 sVNT and PRNT 90 , except for cross-reactivity to SARS-CoV-1 in sVNT.